200 years of the Navier–Stokes equation - Sylvio R. Bistafa (Revista Brasileira de Ensino de Física, 2024)
The year 2022 marked the 200th anniversary of the first appearance of the Navier–Stokes equation, a landmark in Fluid Dynamics introduced by Claude-Louis Navier in 1822. This equation revolutionized the understanding of fluid motion by incorporating viscosity and friction into the equations, expanding their applicability beyond idealized fluids. In this manuscript, we explore the historical development of the Navier–Stokes equation and its profound impact on Fluid Dynamics over the past two centuries. From Navier’s initial insights to George Stokes’ experimental validations and subsequent contributions by other scientists, we trace the evolution of this equation. We also delve into its practical applications, including its role in the development of Computational Fluid Dynamics. The Navier–Stokes equation has played a pivotal role in advancing our understanding of fluid behavior, making it a cornerstone of modern science and engineering.